Caenorhabditis elegans in high-throughput screens for anti-infective compounds. (October 2018) - Peterson, Nicholas D; Pukkila-Worley, Read
Highlights: C. elegans infection models enable high-throughput screens for new anti-infective molecules. Immunostimulatory and anti-virulence compounds can be identified in C. elegans -based screens. Drug screens in C. elegans have identified new classes of antimicrobials that target the pathogen. Anti-infective molecules can be used as probes to define new mechanisms of bacterial pathogenesis. Abstract: New classes of antimicrobials that are effective therapies for infections with multi-drug resistant pathogens are urgently needed. The nematode Caenorhabditis elegans has been incorporated into small molecule screening platforms to identify anti-infective compounds that provide protection of a host during infection. The use of a live animal in these screening systems offers several advantages, including the ability to identify molecules that boost innate immune responses in a manner advantageous to host survival and compounds that disrupt bacterial virulence mechanisms. In addition, new classes of antimicrobials that target the pathogen have been uncovered, as well as interesting chemical probes that can be used to dissect new mechanisms of host–pathogen interactions.